Tissue expression of porcine transient receptor potential mucolipin protein channels and their differential responses to porcine reproductive and respiratory syndrome virus infection in vitro - Xia Zhiqiang; Long Denggao; Hong Xinyi; Lan Ying; Xie Lixia (Journal of Veterinary Research, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) infection results in a serious disease, posing a huge economic threat to the global swine industry. The transient receptor potential mucolipin proteins (TRPMLs) have been shown to be strongly associated with virus infection and other physiological processes in humans, but their tissue distribution and responses to PRRSV in pigs remain unknown.